Three axonal projection routes of individual pyramidal cells in the ventral CA1 hippocampus - Arszovszki, Antónia; Borhegyi, Zsolt; Klausberger, Thomas (Frontiers in Neuroanatomy, 2014)
Pyramidal cells of the ventral hippocampal CA1 area have numerous and diverse distant projections to other brain regions including the temporal and parietal association areas, visual, auditory, olfactory, somatosensory, gustatory, and visceral areas, and inputs to the amygdalar and prefrontal-orbital-agranular insular region. In addition, their differential expression of proteins like calbindin provides further indications for cellular diversity. This raises the possibility that the pyramidal cells may form subpopulations participating in different brain circuitries. To address this hypothesis we applied the juxtacellular labeling technique to fill individual pyramidal cells in the ventral hippocampus with neurobiotin in urethane anaesthetized rats. For each labeled pyramidal cell we determined soma location, dendritic arborisations and selective expression of calbindin and norbin. Reconstruction and mapping of long-range axonal projections were made with the Neurolucida system. We found three major routes of ventral CA1 pyramidal cell projections. The classical pathway run caudo-ventrally across and innervating the subiculum, further to the parahippocampal regions and then to the deep and superficial layers of entorhinal cortex. The other two pathways avoided subiculum by branching from the main axon close to the soma and either travelled antero- and caudo-ventrally to amygdaloid complex, amygdalopiriform-transition area and parahippocampal regions or run antero-dorsally through the fimbria-fornix to the septum, hypothalamus, ventral striatum and olfactory regions. We found that most pyramidal cells investigated used all three major routes to send projecting axons to other brain areas. Our results suggest that the information flow through the ventral hippocampus is distributed by wide axonal projections from the CA1 area.